A simplified model for reinforced concrete beam-column joints under seismic loads - Kang, Shao-Bo (2018)
This paper presents a simplified model for reinforced concrete beam–column joints under seismic loads. In the model, the beams, columns and the joint zone are assumed to remain rigid, and flexural deformations of the beams and column are concentrated at the joint interfaces. The compatibility condition of the joint is established in accordance with the rigid-plastic assumption. To correlate the flexural deformations of the beams and columns to strains of tensile reinforcement, piecewise linear strain profiles of tensile reinforcement are assumed along the beams and columns and slips of embedded reinforcement in the joint are also considered. Thereafter, the plane-section assumption is employed to determine the strain profiles at the joint interfaces. In calculating the compression force in concrete, the stress–strain model for concrete is used instead of the equivalent rectangular concrete compressive stress block. The rigid-plastic model was calibrated against published experimental results of interior and exterior beam–column joints in terms of load–displacement curves. Furthermore, the yield displacement of beam–column joints was calculated and verified by test data. Through the analytical model, forces transferred to the joint zone by tensile, compressive reinforcing bars and concrete can be quantified, which enables further development of the joint model to evaluate the shear resistance of beam–column joints.